The Education and Methodological Complex "Im Klartext A2": Continuity and Innovation - Julia Mueller; Marina Omelchenko (ARPHA Proceedings, 2021)
In the field of professional education, the problem of creating innovative teaching aids and educational and methodological complexes is currently especially acute. The tasks and functions of teaching materials in a foreign language are fundamentally changing and becoming more complicated in connection with the changing requirements of the labour market for young specialists, the duration of study at universities and the increasing informatization and digitalization of processes. It is necessary to critically rethink the experience accumulated in the field of compiling textbooks and education-methodical complexes in foreign languages and optimize their content and structure, taking into account new requirements. The article undertakes a comparative analysis of the classic textbook and the education-methodical complex of the new generation in the German language. The manuals are analyzed from the point of view of the content, the authenticity of the proposed materials and the communicative component of the exercises and tasks. The genres of the texts used and the types of tasks for the extraction of information while reading are highlighted. The results of the analysis showed that the teaching materials of a new type include the most effective traditional types of exercises and tasks, at the same time, the compilers make an attempt to use language and speech exercises comprehensively, lexical and grammar material is worked out in interaction, and the system of exercises is aimed at the formation and improvement of communicative, sociocultural, strategic and pragmatic competencies. The structure of the teaching materials of a new type also includes a program of study in a multimedia class for the development of pronunciation skills using authentic samples of speech and listening skills with full or partial extraction of information from texts of different genres, selected taking into account the level of students and the subject matter of the main parts of the teaching materials.